Compact Circular Polarized Antenna Design With H-Shaped Slots And Stair Notches For Wireless LAN Application Of 2.4 GHz - Kamarul Ariffin, Abd Rashid; Mohd Nor, Husain; Muhammad Majdi, Saad; Mohamad Zoinol Abidin, Abd Aziz; Nornikman, Hassan (Penerbit Universiti, UTeM, 2016)
This paper presents the design of a circular polarized antenna for wireless communication system. Firstly, the linear polarization antenna is simulated in the CST Microwave Studio. This linear polarization antenna is designed by using double H-shaped slots, coplanar waveguide (CPW) and stair notches at the patch techniques. Then, the truncated corners at the patch are designed to create a circular polarization antenna. The dimension of this circular polarization antenna is 28 mm width x 33 mm length. Both antennas are designed for a single frequency operation band at 2.4 GHz. The return-loss performance of the circular polarized antenna is - 46.785 dB and – 39.758 dB for each simulation and measurement respectively.